2018
DOI: 10.1134/s0006297918030021
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Human THP–1 Cell Phagocytic Activity during Macrophagic Differentiation

Abstract: Studies of the role of macrophages in phagocytosis are of great theoretical and practical importance for understanding how these cells are involved in the organism's defense response and in the development of various pathologies. Here we investigated phagocytic plasticity of THP-1 (acute monocytic human leukemia) cells at different stages (days 1, 3, and 7) of phorbol ester (PMA)-induced macrophage differentiation. Analysis of cytokine profiles showed that PMA at a concentration of 100 nM induced development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…We assessed the formation of ASC-specks in cells treated with rHCV-core or purified recombinant green fluorescence protein (rGFP, control). As phagocytic cells, THP-1 macrophages readily internalize cell-free macromolecules in a fashion similar to KCs [27, 55], and immunofluorescence staining of recombinant core or fluorescence analysis of rGFP in cells demonstrated the uptake of each protein by treated THP-1 macrophages. We found that rHCV-core but not rGFP triggered ASC-speck formation after cell uptake (Fig 4C).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the formation of ASC-specks in cells treated with rHCV-core or purified recombinant green fluorescence protein (rGFP, control). As phagocytic cells, THP-1 macrophages readily internalize cell-free macromolecules in a fashion similar to KCs [27, 55], and immunofluorescence staining of recombinant core or fluorescence analysis of rGFP in cells demonstrated the uptake of each protein by treated THP-1 macrophages. We found that rHCV-core but not rGFP triggered ASC-speck formation after cell uptake (Fig 4C).…”
Section: Resultsmentioning
confidence: 99%
“…After inoculation into 96-well microtiter plates at 1 9 10 5 cells per well, macrophages were incubated in colorless DMEM under normal conditions for 24 h prior to the light treatment. Then, macrophages were incubated with zymosan (Sigma-Aldrich, China) for phagocytosis stimulation (100 nM (37)) and/or were irradiated. After 3 or 24 h, the phagocytosis activity was assessed using nitro blue tetrazolium (NBT) reduction test in cells with zymosan.…”
Section: Methodsmentioning
confidence: 99%
“…The light-evoked phagocytosis was compared with activation by an effective dose of zymosan, a known pharmacological stimulator of phagocytosis (Kurynina et al, 2018). Zymosan is used in standard techniques to stimulate the maximum activity of macrophages (e.g., in a generally accepted technique of NBT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…THP-1 cells were cultured in RPMI medium 1640 (GIBCO, Life Technologies Corporation, NY, United States) containing 10% FBS at 37°C in a humidified atmosphere containing 5% CO 2 . Macrophages (Mφ) were acquired from THP-1 cells by induction with 200 ng/ml PMA for 6 h as previously described (Tsai et al, 2017;Kaneko et al, 2018;Kurynina et al, 2018) but with minor modification.…”
Section: Cell Culturesmentioning
confidence: 99%